Assessment of chitosan-based edible coatings containing bioactive compounds derived from agricultural residue for improving postharvest quality characteristics of tomato (Solanum lycopersicum L.) - Yadav, Sujeeta; Malik, Kamla; Sharma, Kashish; Dhillon, Pushpa; Harikarthik, Dandu (Frontiers in Nutrition, 2025)
This study aimed to evaluate the impact of bioactive-based edible coatings on the shelf life of tomatoes. Bioactive compounds were extracted from rice and wheat straw. Different concentrations of phenolic extracts (0.2–1.0 g/mL) were blended with 1% chitosan and applied to fresh tomatoes stored at 28 °C and 74%−84% relative humidity (RH) for 30 days. Periodic evaluations revealed that tomatoes coated with 1.0 g/mL extract of rice and wheat straw coatings were highly effective in maintaining tomato quality as compared to controls. Tomatoes coated with 1.0 g/mL extract of wheat straw exhibited the most favorable results, including delayed weight loss (1.29%), slowed ripening, reduced pH levels, and lower lycopene (2.79 mg/100 g) and beta-carotene (0.62 mg/100 g) contents as compared to those coated with coatings containing rice straw extracts. Additionally, wheat straw extract-coated tomatoes had the lowest disease incidence (2%) after 30 days, as compared to 100% incidence in control samples. Overall, using edible coatings enriched with rice and wheat straw extracts presents a promising approach to extending the shelf life of tomatoes while preserving their nutritional value, inhibiting microbial growth, and offering a more sustainable and eco-friendlier alternative to conventional packaging methods.